Alternative fuels to reduce greenhouse gas emissions from marine transport and promote UN sustainable development goals. (15th April 2023) - Islam Rony, Zahidul; Mofijur, M.; Hasan, M.M.; Rasul, M.G.; Jahirul, M.I.; Forruque Ahmed, Shams; Kalam, M.A.; Anjum Badruddin, Irfan; Yunus Khan, T.M.; Show, Pau-Loke
Graphical abstract: Highlights: Marine emission possesses both environmental and human health risks. Alternative fuels including hydrogen can reduce harmful emissions from marine transport. Alternative fuels have the potential to promote UN Sustainable Development Goals. The potential challenges of alternative fuel in marine transport are highlighted. Abstract: The International Maritime Organization (IMO) has placed stricter controls on several aspects of global maritime transport operations to protect the environment. In light of this, the goal of this study is to examine and assess the different prospective paths and technologies that will assist the shipping industry in decarbonizing its operations. We consider how the utilisation of various alternative energy sources reduces greenhouse gas (GHG) emissions from marine transportation and contributes to the promotion of the United Nations Sustainable Development Goals (SGDs). The complexities associated with maritime industry operations using alternative energy sources are also explored. Biofuel as an alternative energy source, including biomethanol and biodiesel, can reduce greenhouse gas emissions in the shipping industry by 25% to 100%. However, the current supply of biofuels can only meet about 15% of the total demand which is not sufficient to sustainably power the entire marine fleet. There are several issues associated with these biofuels, including oxidation, ecological consequences, feedstock availability, technical and operational constraints, and economic factors that must be addressed before their full potential may be achieved.